2018
DOI: 10.1002/bit.26825
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and assembly of human vault particles in yeast

Abstract: Vault particles are the largest naturally occurring ribonucleoprotein complexes found in the cytoplasm. In all 78 copies of major vault protein (MVP) assemble on polyribosome templates, forming recombinant vault particles, which are of great interest as encapsulation carriers for therapeutics delivery and enzyme stabilization. Baculovirus-insect cell expression is the only system that has been developed for recombinant vault synthesis, but it has low scalability and slow production rate. In this study, we demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Yeast have been successfully used in the last decades for recombinant protein production [64] and, for the synthesis of protein nanostructures such as virus-like particles [65], are similar in size and structure to vaults. In this context, it has been recently described for the first time the production of vaults in the yeast Pichia pastoris [66]. Expression of MVP alone in P. pastoris led to the formation of intact vaults, morphologically similar to endogenous vaults isolated from other eukaryotes.…”
Section: Recombinant Vaults Production and Purificationmentioning
confidence: 99%
“…Yeast have been successfully used in the last decades for recombinant protein production [64] and, for the synthesis of protein nanostructures such as virus-like particles [65], are similar in size and structure to vaults. In this context, it has been recently described for the first time the production of vaults in the yeast Pichia pastoris [66]. Expression of MVP alone in P. pastoris led to the formation of intact vaults, morphologically similar to endogenous vaults isolated from other eukaryotes.…”
Section: Recombinant Vaults Production and Purificationmentioning
confidence: 99%
“…The minimum vault structure, endowed with its natural morphology, can be produced by expression of the sole MVP in insect cells [14,15]. More recently, recombinant vault nanoparticles were produced in the methylotropic yeast Pichia pastoris and were proven to be morphologically indistinguishable from those produced in insect cells [16]. A singular trait of the vault nanoparticle is the way it assembles, as it was shown that biosynthesis and assembling of MVP subunits take place sequentially at the level of polyribosomes, which therefore act similar to a 3D nanoprinter [15].…”
Section: Introductionmentioning
confidence: 99%
“…(H, I) Illustration and AFM image of a DNA origami box encapsulated with proteins. Reproduced with permission from (A) ref , copyright 1992 American Chemical Society; (B) ref , copyright 2006 Wiley; (D) ref , copyright 2014 American Chemical Society; (E) ref , copyright 2012 Nature Publishing Group; (F) ref , copyright 2018 Wiley; (G) ref , copyright 2014 Royal Society of Chemistry; (I) ref , copyright 2012 American Chemical Society.…”
Section: Introductionmentioning
confidence: 99%